Arrangement of Karaoke Venues in the Legal Territory of Demak Regency Based on Demak Regency Regional Regulation Number 11 of 2018 Concerning the Implementation of Entertainment Businesses in Demak Regency - Edi Prianto; Jumadi; Syukron Abdul Kadir; Vicki Dwi Purnomo (Formosa Journal of Social Sciences (FJSS), 2023)
In this cutting edge period, excitement and amusement have ended up an vital portion of people's day by day lives. One prevalent frame of amusement is karaoke. Be that as it may, it is imperative for governments and specialists to guarantee that karaoke settings work concurring to set measures and directions. Setting up a great karaoke setting includes lawful, authorizing, administrative viewpoints, as well as security and security for guests. This paper is based on a survey of writing and pertinent data sources. Rules and controls with respect to the course of action of karaoke settings from different sources such as government specialists, nearby controls, and official archives will be the most premise for composing this paper. A comprehensive approach will be taken to supply a intensive understanding of the course of action of karaoke settings